Effect of planting date on growth, development, and yield of grain sorghum hybrids - Diawara, Bandiougou (Kansas State University, 2012)
In Kansas, productivity of grain sorghum [Sorghum bicolor (L.) Moench] is affected by weather conditions at planting and during pollination. Planting date management and selection of hybrid maturity group can help to avoid severe environmental stresses during these sensitive stages. The hypothesis of the study was that late May planting improves grain sorghum yield, growth and development compared with late June planting. The objectives of this research were to investigate the influence of planting dates on growth, development, and yield of different grain sorghum hybrids, and to determine the optimal planting date and hybrid combination for maximum biomass and grains production. Three sorghum hybrids (early, medium , and late maturing) were planted in late May and late June without irrigation in Kansas at Manhattan/Ashland Bottom Research Station, and Hutchinson in 2010; and at Manhattan/North Farm and Hutchinson in 2011. Data on leaf area index, dry matter production, harvest index, yield and yield components were collected. Grain yield and yield components were influenced by planting date depending on environmental conditions. At Manhattan (2010), greater grain yield, number of heads per plant, harvest index, and leaf-area were obtained with late-June planting compared with late May planting, while at Hutchinson (2010) greater yield was obtained with late May planting for all hybrids. The yield component most affected at Hutchinson was the number of kernels panicle-1 and plant density. Late-May planting was favorable for late maturing hybrid (P84G62) in all locations. However, the yield of early maturing hybrid (DKS 28-05) and medium maturing hybrid (DKS 37-07) was less affected by delayed planting. The effects of planting dates on growth, development, and yield of grain sorghum hybrids were found to be variable among hybrid maturity groups and locations.
Keywords: Sorghum; Hybrid; Planting date; Growth; Agronomy (0285)